2012
DOI: 10.1242/jeb.064592
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of colour adaptation in the prawn Penaeus monodon

Abstract: SUMMARYExposure of prawns to dark-or light-coloured substrates is known to trigger a strong colour adaptation response through expansion or contraction of the colouration structures in the prawn hypodermis. Despite the difference in colour triggered by this adaptive response, total levels of the predominant carotenoid pigment, astaxanthin, are not modified, suggesting that another mechanism is regulating this phenomenon. Astaxanthin binds to a specific protein called crustacyanin (CRCN), and it is the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…Parisenti et al () found that Pacific white shrimp, Litopenaeus vannamei , grown in black tanks were significantly darker than those grown in white tanks. The same response was well documented in the black tiger prawn, Penaeus monodon (Tume et al , Wade et al ). Such observations suggest that these species, as well as L. boggessi , would present darker coloration with less (darker) reflected light.…”
Section: Discussionsupporting
confidence: 72%
“…Parisenti et al () found that Pacific white shrimp, Litopenaeus vannamei , grown in black tanks were significantly darker than those grown in white tanks. The same response was well documented in the black tiger prawn, Penaeus monodon (Tume et al , Wade et al ). Such observations suggest that these species, as well as L. boggessi , would present darker coloration with less (darker) reflected light.…”
Section: Discussionsupporting
confidence: 72%
“…Alternatively, crustacyanin subunit A and C genes might only be responsible for a small change in prawn colour, with other factors having a stronger influence on prawn colouration. The latter is supported by a study carried out by Wade et al [72] that showed a difference in free astaxanthin levels, but not in crustacyanin gene expression levels, when prawns of different colour intensity were compared. In this study colour change was induced in P. monodon by exposure to either a light or a dark background and a consistent difference in colour intensity was detected; however, regulation of this adaptive colour response was not observed at the gene expression level.…”
Section: Discussionmentioning
confidence: 65%
“…The stress of the aquatic organisms can have negative repercussions on their health state and, therefore, on growth; thus, the background colour of the culture system is of great relevance, principally in the larval phases of fish and crustaceans(Cobcroft & Battaglene, 2009;El-Sayed & El-Ghobashy, 2011;Rabbani & Zeng, 2005) Rabbani and Zeng (2005). Crustacyanin is a unique protein to the crustaceans and has a high affinity with astaxanthin which promotes astaxanthin accumulation and changes the expression of colour of the body tissues(Wade et al, 2012). Moreover, it was observed that the dark backgrounds promoted a greater growth rate which was attributed to more efficient feeding as a result of the contrast of the background colour with the prey and the decrease in stress of the larvae.The most relevant result of the present investigation was the effect of the background colour of the experimental unit and the light spectrum on the accumulation of total carotenoids in the cephalothorax of the shrimp.…”
mentioning
confidence: 99%